A novel approach in orthodontics: Archwise distraction osteogenesis - ACAR, YASEMİN BAHAR (My University, 2024)
Distraction osteogenesis can be described as a procedure that is based on the principles of physiologic remodeling and indirect fracture healing. In dentoalveolar level, conventional appliances may present some difficulties such as the need for multiple stages of DO to achieve a good occlusion due to distraction on a straight vector; incompetency to reduce the oronasal fistula in cleft patients; and the difficulty in achieving complete hard and soft tissue reconstruction, especially in cases with large alveolar defects. ArchWise Distraction Appliance (AWDA) have been developed to overcome these limitations and obtain a regenerated bone curvilinear in shape, similar to the original alveolar bone configuration. This article aims to introduce and explain the AWDA method in detail so that every clinician will be able to perform the treatment. The reader can observe the application of the procedure on a variety of cases including cleft lip and palate, trauma, and bone pathology. Possible complications and their solutions are also explained on actual cases.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Ortodonti; Orthodontics; Alveolar distraction osteogenesis; Archwise distraction osteogenesis; Bone regeneration; Dentoalveolar defect; Distraction osteogenesis